PRONE-LATERAL RADIOGRAPHY AND TRANSPERINEAL ULTRASONOGRAPHY IN PEDIATRIC ANAL ATRESIA: AN ALTERNATIVE APPROACH TO DETERMINING - Yuldashev , Muzaffar; Gafurov , Adxam; Toshboev , Sherzod (Medical science of Uzbekistan, 2025)
Recently, some data has emerged regarding the use of ultrasonographic techniques in diagnosing anorectal malformations (ARMs). However, there is a lack of comprehensive scientific research widely covering the results of studies on this technique. Objective. To evaluate the effectiveness of echographic ultrasonography in determining the type of anal atresia in neonates and to assess its applicability in clinical practice. Materials and Methods. The study involved a comparative analysis of the diagnostic sensitivity and accuracy of radiological visualization and ultrasonographic methods for measuring the distance between the rectal pouch and the skin in 27 neonates with anal atresia. In all neonates, invertography, prone-lateral radiography, and transperineal ultrasonography were performed. Results and Discussion. The results indicated that congenital anomalies of the gastrointestinal tract constituted the majority of developmental defects among the studied neonates. Out of 27 patients, 4 cases of fistula and 3 cases of cloacal malformation were excluded from the study due to their specific nature, leaving 20 patients for analysis. Among them, the low type of ARM was found in 13 cases, while intermediate and high types were identified in 7 cases, with 3 and 4 patients, respectively. A receiver operating characteristic (ROC) analysis was conducted to evaluate the specificity and sensitivity of prone-lateral radiography and perineal ultrasonography in diagnosing anal atresia, as well as the informativeness of quantitative tests. The Area Under the Curve (AUC) value for ultrasonography was high (0.92), indicating its superior sensitivity in diagnosing anal atresia, providing correct diagnoses in 92% of cases. The AUC value for prone-lateral radiography was lower (0.58), reflecting its reduced sensitivity and accuracy compared to ultrasonography. Ultrasonography demonstrated a sensitivity of 92.3%, indicating a high probability of correct diagnosis, with a specificity of 85.7%, highlighting its high diagnostic efficiency. In contrast, radiography showed a sensitivity of 15.4%, indicating low detection capability, although it had a specificity of 100%, confirming its accuracy in clear-cut cases. Conclusion. Transperineal ultrasonography can be promptly utilized for the early diagnosis of congenital anorectal anomalies, allowing real-time identification and assessment of anatomical characteristics and aiding in precise surgical planning. Additionally, the lack of radiation exposure makes this technique preferable to radiography.